2009
DOI: 10.1002/elan.200804577
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Silver Nanoparticles on Carbon Ionic Liquid Electrode for Electrocatalytic Sensing of Hydrogen Peroxide

Abstract: Silver nanoparticles (narrowly dispersed in diameter) were electrodeposited on carbon ionic liquid electrode (CILE) surface using a two-step potentiostatic method. Potentiostatic double pulse technique was used as a suitable and simple method for controlling the size and morphologies of silver nanoparticles electrodeposited on CILE. The obtained silver nanoparticles deposited on CILE surface showed excellent electrocatalytic activity (low overpotential of À 0.35 V vs. Ag/AgCl) towards reduction of hydrogen per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 52 publications
1
44
0
3
Order By: Relevance
“…The combined existence of GNPs within CSNFs NW provides the excellent performance of the biosensor towards the electrochemical detection of cholesterol. Many researchers have reported the inclusion of metal nanoparticles with a catalytic effect in polymer modified electrodes to decrease the overpotential applied to the amperometric biosensors (Safavi et al, 2009, Hrapovic et al, 2004, Ren et al, 2005, Huang et al, 2004. Amperometric cholesterol biosensors based on carbon nanotube-chitosan-platinumcholesterol oxidase nanobiocomposite was fabricated for cholesterol determination at an applied potential of 0.4 V (Tsai et al, 2008).…”
Section: Cholesterol Biosensorsmentioning
confidence: 99%
“…The combined existence of GNPs within CSNFs NW provides the excellent performance of the biosensor towards the electrochemical detection of cholesterol. Many researchers have reported the inclusion of metal nanoparticles with a catalytic effect in polymer modified electrodes to decrease the overpotential applied to the amperometric biosensors (Safavi et al, 2009, Hrapovic et al, 2004, Ren et al, 2005, Huang et al, 2004. Amperometric cholesterol biosensors based on carbon nanotube-chitosan-platinumcholesterol oxidase nanobiocomposite was fabricated for cholesterol determination at an applied potential of 0.4 V (Tsai et al, 2008).…”
Section: Cholesterol Biosensorsmentioning
confidence: 99%
“…The method permits deposition of high-purity metal nanoparticles on substrates of varying sizes and shapes, with greater control over the density [22]. In continuation to our previous reports on PEC splitting of water, using nanostructured undoped/doped metal oxides, the present work is an endeavor to enhance the PEC performance of [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 78%
“…[21][22][23] Yang et al [24] obtained silver microdendrites by one-step synthesized as novel separation mediums, the resulted silver micro-dendrites were applied in multi-DNA analysis. Safavi et al [25] electrodeposited AgNPs on carbon ionic liquid electrode surface through a two-step potentiostatic method for electrocatalytic sensing of H 2 O 2 . Moreover, Geng et al [26] have proposed a physical vapor deposition method to form AgNPs, and found that the obtained AgNPs could improve the signals of surface enhanced Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%